Pemikiran Fiqih Moderat di Timur Tengah dan Relasinya dengan Gerakan Fiqih Formalis - Abdad, M. Zaidi (ISLAMICA: Jurnal Studi Keislaman, 2011)
Islamic thought has conventionally distinguished between what it calls the People of Hadith (ahlu al-hadÃ®s) and the People of Opinion (ahl ar-raây). These two segments have improved into a countless current of thought in the modern world, making it impossible to refer to a certain type of thinking as this or that. Nonetheless, the basic characters of the modern Muslim thinking are not quite distinctive from that of the classical-dualistic dichotomy. Hence, the clash of discourse that we witnessed recently in various Muslim worlds is reflective of the intellectual tension between the People of Hadith and the People of Opinion. The clash of discourse that we have just referred to even took the form of physical conflict such as that which happened in Egypt and Algeria. In these two Muslim countries the clash of discourse has turned into the clash of politics, where religious radicalism and absolutism are the dominant features. This paper seeks to provide a critique of this negative development, offering in the process a kind of discourse that can serve as an alternative, namely the discourse of a moderate Islam.